(untitled) (Journal of the College of Basic Education, 2026)
There is no disagreement among scholars that the miraculous nature of the Qur’an lies in its style, the precision of its words, and the harmony and consistency between the word and the intended meaning, such that the word portrays the meanings with the utmost accuracy. This research addresses whether translation is the Qur’an or not. It discusses the jurisprudential opinions on the permissibility of translation, considering it as an interpretation of the Qur’an’s meanings. It then examines whether translation has influenced Islamic thought, directly or indirectly, and whether it is correct to say that translation is the Qur’an or not. The research discusses the jurisprudential opinions on the permissibility of translation, considering it as an interpretation of the Qur’an’s meanings, and concludes that the translation of the Qur’an is present within the Qur’an itself through the transmission of the ideas, stories, opinions, speech, and details of the lives of previous nations from different languages ​​into the language of the Qur’an. This is the best evidence that translation is permissible.